Assessing shift in breast cancer stage from the anatomical staging classification to the clinical prognostic staging system - Rahmiz R. Thomas; Tahlia Naidoo; Uchechukwu A.N. Izegbu; Neo H. Mabe; Tanya Augustine; Jenny Edge (South African Journal of Oncology, 2026)
Background: Breast cancer is the most frequently diagnosed malignancy among women and a significant health burden in South Africa. The American Joint Committee on Cancer (AJCC) 8th Edition incorporates biological markers (oestrogen receptor, progesterone receptor, human epidermal growth factor receptor 2 [HER2] status and tumour grade) into conventional tumour, node, metastasis staging. Evidence from low-income and middle-income settings with high HIV prevalence remains limited. Aim: We compared the anatomical staging (AJCC 7th Edition) with the clinical prognostic staging (AJCC 8th Edition) at a South African tertiary centre, and evaluated stage migration by tumour biology, HIV status and demographics. Setting: Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). Methods: We conducted a retrospective review of 524 newly diagnosed patients with breast cancer at CMJAH. Clinical records, pathology, and imaging were used to assign anatomical and clinical prognostic stages. Associations among stage migration and molecular subtype, HIV status, and age were assessed. Results: Overall, 33.8% of patients experienced stage migration. Downstaging was most frequent in Luminal A (28.1%) and Luminal B HER2+ (34.1%); upstaging predominated in triple-negative breast cancer (69.4%). Application of the clinical prognostic model reclassified an additional 8% as Stage I, with a 5% and 2% decline in Stage II and Stage III disease, respectively. Stage IV disease did not change. HIV prevalence was 15.65% and showed no association with migration (p > 0.05). Conclusion: Incorporating biological markers substantially reclassifies patients, especially among hormone receptor-positive and triple-negative subtypes, with direct implications for treatment planning. Contribution: These findings support routine adoption of biologically informed staging in South Africa.